A Short-term Analysis of Hydrogen Demand and Refueling Station Cost in Shenzhen China. (December 2016) - Liu, Xiaotong; Zhang, Shuyang; Dong, Jun; Xu, Xinhai
Abstract: The deployment of fuel cell vehicles in Shenzhen, China is far behind electric vehicles. In order to promote the application of fuel cell vehicles, significant efforts are required to construct hydrogen stations in the near future. The present study focused on the estimation of hydrogen demand and refueling station cost in Shenzhen between 2016 and 2025. Three scenarios of fuel cell vehicle penetration rate in the new car market were employed to predict the fuel cell vehicle number and daily hydrogen demand. Capital investment and operation and maintenance cost of on-site steam methane reforming hydrogen fueling stations were studied. The capital cost of a 1000 kg H2 /day hydrogen refueling station was calculated as $ 7.84 million. Hydrogen fuel price of different size fueling stations at various years of return on investment were also compared. The lowest H2 price can be reached is $6.78/kg.